Clinical, Radiographic, and Histologic Evaluation of Maxillary Sinus Lift Procedure Using a Highly Purified Xenogenic Graft (Laddec®) - Renzo Guarnieri; Fabrizio Belleggia; Stefano Ippoliti; Patrica DeVilliers; Luigi Vito Stefanelli; Stefano Di Carlo; Giorgio Pompa (eJournal of Oral Maxillofacial Research)
Objectives: The aim of this study was to evaluate the clinical, radiographic and histologic results when a highly purified xenogenic bone (Laddec®) was used as grafting material in maxillary sinuses.